Educating lives for Christian wisdom - Davis, Darin H. (International journal of Christianity & education, 2016)
This article explores how educating lives for Christian wisdom might serve as an antidote to the vice of acedia, a prominent feature of the culture of contemporary higher education. After suggesting that the capital vice of acedia seems to capture well various facets of our present age and how the pursuit of wisdom serves as its antidote, we examine important practices and virtues that sustain the quest for Christian wisdom as distinct from practical and theoretical wisdom. In particular, we discuss worship, wonder and delight, humility and prayer, charitable reading, and friendship.